A new class of N-doped ionic PAHs via intramolecular [4+2]-cycloaddition between arylpyridines and alkynes - Mule, Ravindra D.; Shaikh, Aslam C.; Gade, Amol B.; Patil, Nitin T. (Chemical Communications, 2018)
Reported herein, for the first time, is a copper-promoted intramolecular [4+2]-cycloaddition cascade to access ionic N-doped polycyclic aromatic hydrocarbons (PAHs) with tunable emission wavelengths. It is shown that the reaction can be made catalytic with respect to Cu(OTf)(2) when an external oxidant, Selectfluor, was used.